2020
DOI: 10.3390/ijms21228691
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic Reconstruction and Analysis of Gene Networks Related to Glucose Variability in Diabetes and Its Complications

Abstract: Glucose variability (GV) has been recognized recently as a promoter of complications and therapeutic targets in diabetes. The aim of this study was to reconstruct and analyze gene networks related to GV in diabetes and its complications. For network analysis, we used the ANDSystem that provides automatic network reconstruction and analysis based on text mining. The network of GV consisted of 37 genes/proteins associated with both hyperglycemia and hypoglycemia. Cardiovascular system, pancreas, adipose and musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 124 publications
1
23
0
1
Order By: Relevance
“…The network consisted of 37 genes/proteins associated with both hyperglycemia and hypoglycemia. GV-related molecules were involved in glucose metabolism, intracellular signaling, cell proliferation and other biochemical/physiological processes; they were identified in the central positions of the gene networks of diabetic vascular complications [161].…”
Section: Gene Expressionmentioning
confidence: 99%
“…The network consisted of 37 genes/proteins associated with both hyperglycemia and hypoglycemia. GV-related molecules were involved in glucose metabolism, intracellular signaling, cell proliferation and other biochemical/physiological processes; they were identified in the central positions of the gene networks of diabetic vascular complications [161].…”
Section: Gene Expressionmentioning
confidence: 99%
“…For example, one prior study identified Prenylcysteine oxidase 1 (PCYOX1), beta-ala-his dipeptidase (CNDP1), and extracellular matrix protein 1 (ECM1) as valuable diagnostic biomarkers associated with the incidence of gestational diabetes [17]. Saik et al further found the JAK-STAT, MAPK, and protein kinase B signaling pathway to be closely linked to diabetes complications and hypoxia responses [18]. The GO and KEGG analyses conducted in this study suggested the top DEGs to be enriched in sarcomere organization, muscle filament sliding, and the regulation of cardiac conduction, potentially playing a role in regulating angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, FN1, a gene involved in cell adhesion and migration processes, including embryogenesis, wound healing, blood coagulation, host defense, and metastasis, appears to be the centre of the PPI network. Previous studies suggested that FN1 is a major ECM component secreted by various epithelial or mesenchymal cell types in both physiologic and pathophysiologic situations in response to high glucose stimulations [22][23][24].…”
Section: Identification and Annotation Of Genes Related To Tnbc-specific Glucose Metabolismmentioning
confidence: 99%